Revisiting Black Mountain College: Teaching to Transgress - Richter, Dorothee (Farol, 2021)
Every art university wants to give its graduates the greatest opportunities after graduation, as artists, curators, actors, conductors, musicians, designers, filmmakers, or dancers. How to get from A to Z in this project is based on the respective creativity concept. Do you want to equip the students with management knowledge in order to pave their way into the creative industries? Do you want to provide them with expertise in their field, or is critical thinking required above all, as well as the ability to cooperate that enables students to survive in an extremely complex world?